Depth of cure of the bulk fill resin composite from different light source (Research, Society and Development, 2020)
To evaluate whether Bulk-Fill composite resins (Paste and Flowable) have similar depth of cure varying the light source. Resin composite groups: (P) Paste: FiltekTM One Bulk Fill (F1), Tetric N-Ceram Bulk Fill (T1); Aura Bulk Fill (A1); OPUS Bulk Fill (O1) and (F) Flowable: FiltekTM Bulk Fill Flow (F2); Tetric N-Flow Bulk Fill (T2); SDR® Plus Bulk Fill Flowable (S2); OPUS Bulk Fill Flow (O2). Three discs from each group were made (ISO 4049/2000),in one mold with (4x10mm) was filled with resin and light cured for 20s, varying the light source: Gnatus (G) and Kavo (K). The samples were removed immediately and the uncured portion was removed with a plastic spatula. The measurement was performed with a micrometer ± 0.1mm and the value divided by 2. The data were analyzed using ANOVA One-Way and ANOVA Two-Way followed by t-test with significance of 0.05. The groups (T1-K, S1-K, F1-K, F1-G, F2-G and T1-G) had an acceptable depth recommended by the manufacturer. Between the light sources K and G there is no difference (p = 0.068), more differences has found between the groups (O2-G) (O2-K) (p = 0.004). No differences were found between the group PK (p = 0.059), but showed for group FK (p =